Improvement of Conflict Resolution Among Elementary School Students - Yumahendra, Zefly; Bunyamin Maftuh (Universitas Pendidikan Ganesha, 2024)
Resolving conflict underpins teachers' efforts to improve students' skills in handling personal challenges. It is known that conflicts often stem from social interactions between students in the school environment, highlighting the need for various strategies to address these issues effectively. Based on this, this research aims to analyze an event in more depth, including individual and procedural data, using existing information. This research applies a qualitative research design, namely a case study. The subjects involved are students of the target school. The researcher acts as the main instrument in this qualitative research. The data collection methods used include observation, interviews, and literature observation. The technique used to analyze the data is qualitative-descriptive analysis. The study results are student control and discipline, principals, and instructors participate in resolving and managing conflicts in the education system. Conflict arises when a group of people deviates from their overwhelming desire for control, prestige, or power. When helping students resolve conflicts effectively and non-violently, the educational environment is advised to provide them with conflict resolution skills. These skills can be acquired through various extracurricular activities and other subjects. This study has implications in providing a more comprehensive insight into conflict among elementary school students. It can assist teachers in designing more effective strategies to improve school conflict resolution.